The Impact of Education and Leadership Training on Civil Servants at North Sulawesi Campus of IPDN - Papea, Oudy Oktavianus; Lumingkewas, Lexie; Mokat, Jetty (Technium Social Sciences Journal, 2023)
This research aims to (1) determine the impact of education and leadership training attended by employees of IPDN Sulawesi Utara Campus in terms of the improvement of competencies that occur after the training, and (2) identify and analyze the factors that contribute to the suboptimal outcomes of leadership education and training attended by civil servants in achieving organizational goals at IPDN Sulawesi Utara Campus. This study is qualitative research with a descriptive approach, which involves analyzing and explaining phenomena in-depth through data collection. Data was collected using two sources: primary data obtained through interviews and observations, and secondary data obtained through literature review and documentation. Data analysis was performed by categorizing the data, synthesizing it, identifying patterns, selecting important information to be studied, and drawing conclusions. The research findings indicate that the process of education and leadership training attended by employees of IPDN Sulawesi Utara Campus has a positive impact and fulfills the training objectives stated in Government Regulation Number 101 of 2000 regarding Education and Training in Positions. This is reflected in the improvement of knowledge, skills, and attitudes (KSA), broadened perspectives, high motivation and professionalism as civil servants, shared vision aligned with organizational goals, and rational mindset. Based on these success indicators, it can be concluded that the education and training process has provided positive impacts on employees, the organization, and public services.